Performance Factors of Industrialised Building System (IBS) and Conventional Method Toward Sustainable Construction - Mazlan, Farahhanum; Yasin, Ir. Dr. Mohd Norazam (Recent Trends in Civil Engineering and Built Environment, 2023)
The Industrialised Building System (IBS) was introduced as a replacement for the conventional system and in response to the government’s ideas for sustainable development. IBS provides advantages such as labour savings, high quality, and faster completion time. In contrast, conventional methods are vulnerable to flaws in terms of quality, effectiveness, and reliance on foreign workers. However, many industry players are still unwilling to abandon the conventional way. The study’s objectives are to investigate the issues and challenges associated with IBS and conventional methods, to identify performance factors associated with IBS and conventional methods, and to analyse the issues/challenges and performance of IBS and conventional methods in terms of sustainability. A total of 36 questionnaires were analysed using the Statistical Package for Social Science (SPSS) software, with a 5-point Likert scale used to determine the respondents’ level of agreement. According to the findings of this study, conventional methods and IBS face five and 23 issues and challenges, respectively. The performance factor is made up of six components: cost, quality, time, social, environmental, and economic. These components were also discussed in the data analysis. This result of this study helped provide awareness to industry players on the IBS system through performance analysis for IBS and conventional methods.